2022
DOI: 10.1038/s42003-022-04048-7
|View full text |Cite
|
Sign up to set email alerts
|

A ventral stream-prefrontal cortex processing cascade enables working memory gating dynamics

Abstract: The representation of incoming information, goals and the flexible processing of these are required for cognitive control. Efficient mechanisms are needed to decide when it is important that novel information enters working memory (WM) and when these WM ‘gates’ have to be closed. Compared to neural foundations of maintaining information in WM, considerably less is known about what neural mechanisms underlie the representational dynamics during WM gating. Using different EEG analysis methods, we trace the path … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…Beyond motor control and sequence processing, 36 the SMA is essential in WM maintenance and updating 37 , 38 , 39 , 40 as well as cognitive flexibility (task switching) 41 and has previously been shown to be involved in WM gating. 10 , 12 The current finding that the SMA is only involved in gate closing is in line with the role of theta band activity in medial and superior frontal cortices to support cognitive control. 42 , 43 , 44 , 45 , 46 , 47 , 48 Cognitive control is central for shielding information stored in WM, and this is what WM gate closing is about.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Beyond motor control and sequence processing, 36 the SMA is essential in WM maintenance and updating 37 , 38 , 39 , 40 as well as cognitive flexibility (task switching) 41 and has previously been shown to be involved in WM gating. 10 , 12 The current finding that the SMA is only involved in gate closing is in line with the role of theta band activity in medial and superior frontal cortices to support cognitive control. 42 , 43 , 44 , 45 , 46 , 47 , 48 Cognitive control is central for shielding information stored in WM, and this is what WM gate closing is about.…”
Section: Discussionsupporting
confidence: 78%
“… 2 , 3 , 4 The closed state is assumed to reflect the default WM state, which allows the maintenance of representation through shielding WM from distraction. 5 , 6 So far, several studies have showed WM gate opening and closing effects and delineated some underlying neural principles, 7 , 8 , 9 , 10 , 11 , 12 which are triggered by useful or distracting perceptual information, respectively. 13 However, it is still unclear how the decision to open or close the WM gate is implemented on a computational neural level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The group‐ICA was employed to analyze EEG data and extract subcomponents, as done in previous work (Gholamipourbarogh et al, 2022; Gholamipourbarogh et al, 2023; Yu et al, 2022). The use of group‐ICA was motivated by the fact that traditional ICA is not directly applicable to group data, as it estimates different sets of components for each individual or run, making it challenging to draw inferences about the entire group.…”
Section: Methodsmentioning
confidence: 99%
“…We employed the MVPA light toolbox to conduct MVPA on the back‐projected matching component pairs obtained from the CORRMAP results (Yu et al, 2022). At the single‐subject level, two analyses were performed: a binary classification to identify time points with different patterns between IC pairs for congruent and incongruent trials and a temporal generalization analysis to examine the temporal dynamics of the representational content at the component ERP level.…”
Section: Methodsmentioning
confidence: 99%